Círculos de controle da qualidade: um estudo de caso em uma empresa do setor automativo - Palma, Gustavo Imakawa Monteiro da (Brasil, 2024)
This article analyzes the Quality Management of a company that supplies engine parts to the automotive sector. The case study was developed using exploratory criteria, since the researcher collected the necessary information within the company from bibliographical consultations and the application of quality control circles to people involved with the company's shipping. The article intends to study the internal characteristics of the company, giving priority to information on people training and production processes capable of delivering results to the company. Quality control circles is a program used by quality management with the aim of identifying and solving problems within companies and organizations. From the analysis it was also possible to identify improvements.